The complete mitochondrial genome of Pampus minor (Liu & Li, 1998) (Perciformes: Stromateidae) - Shouqiang Wang; Linlin Zhao; Yuan Li; Zhaohui Zhang; Zongling Wang; Tianxiang Gao (Mitochondrial DNA. Part B. Resources, 2019)
In this study, the complete mitochondrial genome sequence of Pampus minor has been determined by long polymerase chain reaction and primer walking methods. The mitochondrial genome is a circular molecule of 16,690 bp in length, including the typical structure of 13 protein-coding genes, two ribosomal RNA genes, 22 transfer RNA genes, and two non-coding regions (L-strand replication origin and control region), the gene contents of which are identical to those observed in most bony fishes. The overall base composition of the heavy strand shows 29.9% of T, 24.7% of C, 30.6% of A and 14.7% of G, with a slight A + T rich feature (60.5%). Within the control region, we identified the termination-associated sequence domain (TAS), and the conserved sequence block domains.